A reflection on traditional Dusun copper-smithing: Saring as literary work / Mohd Iqbal Hashim - Hashim, Mohd Iqbal (2023)
This essay is an academic extension to my participatory immersion as a coppersmith whose praxis centered on cultural revival. An ethnographic experiential reflection of the sort, this essay will propose a discourse on Dusun brassware - henceforth called saring - as a literary work beyond being an object culture. This essay used saring interchangeably to refer to traditional and contemporary brass cultural object. As a student-in-orientation to a Dusun revivalist coppersmith, I learned the art of cold working copper which was practised by the Dusun traditionally. In addition, interaction with other practitioners studying the same subject contributed significantly to the mediation during the saring production. Both methods were followed by corroborating the insights with the existing literature on the Dusun oral culture.